Avances de la Teoría de Alfred Marshall en los Distritos Industriales. Un Estudio Histórico - Guamán Huaraca, Anthony Israel (2024)
ABSTRACT: The aim of this research is to determine the advances of Alfred Marshall's theory on Industrial Districts based on a historical review in Latin America, through the analysis of literature and the application of the Delphi method. For this work a group of experts were involved, for the selection of papers, Scopus platform was used with the keywords in the search, studies of industrial districts since it is Alfred Marshall's theory from the perspective of Latin America. The results found establish that experts recognize that significant advances have been registered in Latin America thanks to the application of Alfred Marshall's theory. Its focus on business collaboration, geographic proximity and the formation of industrial districts has boosted regional economic development remarkably. Although challenges remain, the adaptation of these principles to the specific realities of each country has proven its relevance, especially in key sectors such as manufacturing and tourism. It is essential to continue applying and adapting Marshall's theory to realize its potential and foster sustainable economic growth in the region.